FACTORS AFFECTING THE ESTABLISHMENT AND PRACTICE OF TEAMWORK OF TEACHERS - RAHUL KUMAR SINHA (International Journal of Multidisciplinary Research and Studies, 2020)
The ineffective pursuit of corporate goals can be traced back to a lack of collaborative effort among employees. There is a potential for roadblocks to be placed in the way of efficient cooperation in the educational setting if administrators and instructors do not collaborate effectively with one another and if they have significant philosophical divergences regarding the issues confronting the institution. According to the argument presented by Arcaro in Coleman and Glover (2010:103), "... teams need to be aware of the limits impeding or promoting their success." The economic, cultural, political, personal, and institutional contexts within which the team is intended to grow all serve as restrictions that make it difficult for teachers and school administrators to work together effectively as a team. "Communication, power, influence, authority, motivation, and manipulation are all key interactions inside an organisation, particularly between superiors and subordinates," argue Lunenburg and Ornstein (2012:8) in the human relations approach. It should not come as a surprise at all to find educators or administrators being so self-centered as to accomplish things on their own, thereby piling on an excessive amount of tasks, rendering themselves useless, and even finally falling ill as a result.